(untitled) (Revista Direitos Humanos e Democracia, 2024)
Boaventura de Sousa Santos’ vast work is permeated by his indignation at the socioeconomic differences between territories and between people. “The Law of the Oppressed”, one of his books, portrays how far democracy and justice are from formal law. “Globalization: fatality or utopia?” a book with a series of articles organized by Boaventura shows how globalization with its perverse face has created and widened abysmal lines between people. Therefore, reading Boaventura’s work is essential for anyone who wants to understand the process of inequality at both a local and global level. The review presented in this text is based on one of his lectures where he proposes a reflection on human rights and democracy. If many have already read his work, my proposal here is to reflect on his speech, where I make comments on the topics covered in the lecture, taking into account the tone of his voice and facial expression, which we can hardly understand from books. Therefore, the proposal to read what Boaventura de Sousa Santos said and you did not read.